Gambaran Tingkat Pengetahuan Remaja Putri tentang Perubahan Fisik Masa Pubertas Kelas VII - Nursiah, Wa Ode (Jurnal Sains & Kesehatan, 2022)
Description of the Knowledge Level of Young Women About Physical Changes during Puberty for Class VII. Adolescence is a period of transition in life where at this phase the individual experiences changes from children to adults, including physical changes. Adolescent physical changes are the main characteristic of biological processes that occur rapidly, which are not balanced with psychological changes (mental emotional). The purpose of this study was to describe the level of knowledge of young women about physical changes during puberty in grade VII at SMP Negeri 4 Baubau City in 2021. The type of research used was a descriptive survey research. The population in this study were 194 grade VII adolescent girls at SMP Negeri 4 Baubau City. The number of samples in this study was 55 people, the sampling used the Lameshow formula. The results showed that of the 55 respondents of seventh grade teenage girls at SMP Negeri 4 Baubau, it was found that the level of good knowledge was 15 respondents (27.2%), and the high level of knowledge was 15 respondents (27.2%). lack of knowledge amounted to 40 respondents (72.8%). The conclusion in this study is that it is hoped that adolescents will be more responsible for themselves and their surroundings by increasing their knowledge of physical changes during puberty.